2002
DOI: 10.1097/00006254-200209000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia. Part 1: Clinical and Pathophysiologic Considerations

Abstract: Preeclampsia-eclampsia is still one of the leading causes of maternal and fetal morbidity and mortality. Despite active research for many years, the etiology of this disorder exclusive to human pregnancy is an enigma. Recent evidence suggests there may be several underlying causes or predispositions leading to the signs of hypertension, proteinuria, and edema, findings that allow us to make the diagnosis of the "syndrome" of preeclampsia. Despite improved prenatal care, severe preeclampsia and eclampsia still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
33

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 162 publications
0
80
0
33
Order By: Relevance
“…Circulating levels of MBG have been reported to be increased in patients with volume expansion-mediated hypertension and preeclampsia (5)(6)(7)(8). Preeclampsia is a syndrome that occurs in 3-10% of pregnancies (9,10) and is a leading cause of maternal and fetal morbidity and mortality (9). Preeclampsia is characterized by the de novo development of hypertension and proteinuria after 20 weeks of gestation (9,11).…”
Section: Marinobufagenin (Mbg)mentioning
confidence: 99%
“…Circulating levels of MBG have been reported to be increased in patients with volume expansion-mediated hypertension and preeclampsia (5)(6)(7)(8). Preeclampsia is a syndrome that occurs in 3-10% of pregnancies (9,10) and is a leading cause of maternal and fetal morbidity and mortality (9). Preeclampsia is characterized by the de novo development of hypertension and proteinuria after 20 weeks of gestation (9,11).…”
Section: Marinobufagenin (Mbg)mentioning
confidence: 99%
“…In these and other causes of nephrolithiasis, the site of the initial solid phase has long been the subject of debate. Over 65 years ago, A. Randall demonstrated that interstitial crystals located at, or adjacent to, the papillary tip, Randall's plaques, were common in stone formers (2). He found that these crystals were composed not of calcium oxalate, the most common solid phase found in patients with nephrolithiasis, but of calcium phosphate (3).…”
Section: Altered Angiogenic Balance Causes General Endothelial Dysfunmentioning
confidence: 99%
“…Preeclampsia, or the condition preceding full-blown eclampsia, affects up to 5% of pregnant women and is diagnosed by the onset of hypertension and proteinuria in the second trimester (1). Preeclampsia may eventually progress to glomerular malfunction, thrombocytopenia, liver and brain edema, and associated lifethreatening seizures (2) (Figure 1). Preeclampsia has been sometimes termed the "disease of theories," as several models for its pathogenesis have been proposed.…”
mentioning
confidence: 99%
“…It is specific to human pregnancy and complicate 6 -8 % of gestation after week 20 1 . Preeclampsia is still one of the leading causes of maternal and fetal morbidity and mortality 2 . The pathophysiological mechanism is characterized by a failure of the trophoblastic invasion of the spiral arteries which may be associated with an increased vascular resistance of the uterine artery and a decreased perfusion of the placenta 3 .…”
Section: Introduction:-mentioning
confidence: 99%